The musical legacy of the 1918 Finnish Civil War on YouTube: reconciliation and agitation - Heimo Anne; Mustamo Aila; Rantanen Saija-Leena (Linköping University Electronic Press, 2022)
Conflicts such as wars, rebellions and revolutions often give rise to songs that pass on from one generation to another. This applies also to the bloody 1918 Finnish Civil War, which led to the death of nearly 37 000 people (about 1% of the population), of whom the majority 27 000 belonged to the defeated, the Reds, and affected Finnish society on every level and in long-lasting ways, some of which can still be acknowledged today. For decades after the war official and public commemoration of the war dead applied only to the winners, the Whites, whereas the Reds were forced to mourn and honour their dead in the private sphere. On both sides, songs were first a popular way of keeping up spirits and then after the war to commemorate the war. These songs were sung at funerals, parades as well as to mock the enemy. Today some of these songs as well as new ones on the topic are still popular and circulate in various versions on YouTube and other social media sites. These music videos are often remixes of original footage and photos used together with images from other sources. The most popular videos have been viewed hundreds of thousands of times. In this article, we explore the digital heritage of the 1918 Finnish Civil War by giving first an overview of the musical legacy of the war and then analyse how and why this musical legacy continues to flourish on YouTube.